(untitled) (Global Journal of Management and Business Research, 2022)
The proliferation of financial scandals in recent decades has caused major changes both in the financial sector and in the economy in general, leading to a tightening of the rules for assessing financial equilibrium, assessing health and financial profitability of companies. In this context marked by the exacerbation of a terrible pandemic (covid-19) which is fundamentally upsetting managerial practices, the search for reliable sources of information becomes a necessity for survival. Also, the audit report appears to be a reliable, credible source of information likely to improve business decision-making.